They live in the land down under: thyroid function and basal metabolic rate in the Blind Mole Rat, Spalax. (February 2014) - Avivi, Aaron; Nevo, Eviatar; Cohen, Keren; Sotnichenko, Nick; Hercbergs, Aleck; Band, Mark; Davis, Paul J.; Ellis, Martin; Ashur-Fabian, Osnat
Abstract The Israeli blind subterranean mole rat (Spalax ehrenbergi superspecies) lives in sealed underground burrows under extreme, hypoxic conditions. The four Israeli Spalax allospecies have adapted to different climates, the cool–humid (Spalax galili, 2 n = 52 chromosomes), semihumid (S. golani, 2 n = 54) north regions, warm–humid (S. carmeli, 2 n = 58) central region and the warm–dry S. judaei, 2 n = 60) southern regions. A dramatic interspecies decline in basal metabolic rate (BMR) from north to south, even after years of captivity, indicates a genetic basis for this BMR trait. We examined the possibility that the genetically-conditioned interspecies BMR difference was expressed via circulating thyroid hormone. An unexpected north to south increase in serum free thyroxine (FT4) and total 3, 5, 3′-triiodo-L-thyronine (T3) (p < 0.02) correlated negatively with previously published BMR measurements. The increases in serum FT4 and T3 were symmetrical, so that the T3:FT4 ratio – interpretable as an index of conversion of T4 to T3 in nonthyroidal tissues – did not support relative decrease in production of T3 as a contributor to BMR. Increased north-to-south serum FT4 and T3 levels also correlated negatively with hemoglobin/hematocrit. North-to-south adaptations in spalacids include decreased BMR and hematocrit/hemoglobin in the face of increasing thyroid hormone levels, arguing for independent control of hormone secretion and BMR/hematocrit/hemoglobin. But the significant inverse relationship between thyroid hormone levels and BMR/hematocrit/hemoglobin is also consistent with a degree of cellular resistance to thyroid hormone action that protects against hormone-induced increase in oxygen consumption in a hostile, hypoxic environment.